Volume 10: Ocean Renewable Energy 2018
DOI: 10.1115/omae2018-78067
|View full text |Cite
|
Sign up to set email alerts
|

Non Linear Simulation of a Wave Energy Converter With Multiple Degrees of Freedom Using a Harmonic Balance Method

Abstract: Computationally efficient simulation methods for wave energy converters (WECs) are useful in a variety of applications. The simulation task is particularly challenging when non-linearities are present in the WEC model. Using a Fourier projection of the system inputs and variables, harmonic balance (HB) is a computationally-efficient method to solve for the steady-state motion of a non-linear system, preserving an accurate representation of the non-linear effects. In previous work, HB has been used for the simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…However, for an example case with Coulomb damping in the PTO and a correspondingly non-smooth WEC output, the NLFD takes a long time to converge, and in fact, takes longer than the RK2 integrator and does not achieve the same level of accuracy. The NLFD method is extended to multiple DoF in Novo et al [342], considering the pitching hull motion and the internal gyroscope dynamics of the ISWEC device operating at a site in the Mediterranean Sea as a case study. The study showed that the NLFD method is sensitive to the algorithm starting point and found for some highly energetic sea states the method did not converge.…”
Section: Nonlinear Frequency Domainmentioning
confidence: 99%
“…However, for an example case with Coulomb damping in the PTO and a correspondingly non-smooth WEC output, the NLFD takes a long time to converge, and in fact, takes longer than the RK2 integrator and does not achieve the same level of accuracy. The NLFD method is extended to multiple DoF in Novo et al [342], considering the pitching hull motion and the internal gyroscope dynamics of the ISWEC device operating at a site in the Mediterranean Sea as a case study. The study showed that the NLFD method is sensitive to the algorithm starting point and found for some highly energetic sea states the method did not converge.…”
Section: Nonlinear Frequency Domainmentioning
confidence: 99%
“…The PTO is an electrical torque generator connected to the gyroscope support frame through a gearbox with a gear ratio 1/10. The maximum energy extraction rate is obtained by properly tuning the flywheel spinning speed with the incoming sea state and controlling the PTO torque [35].…”
Section: Iswec Devicementioning
confidence: 99%
“…A practical implementation of an all-encompassing design optimisation is challenging, mainly due to the vast multi-dimensional search space which cannot be tackled with conventional global optimisation approaches due to computational limitations. Moreover, often there is no analytical representation of the relationship between input and output variables, due to hydrodynamic curves defined by points through panel-based simulations (BEM) and implicit nonlinearities requiring simulation via time-advancing schemes [17], or in some conditions, harmonic balance [18]. Therefore, both cost function and constraints usually behave as grey or black boxes.…”
Section: Introductionmentioning
confidence: 99%